Mechanisms of Key Innate Immune Cells in Early- and Late-Onset Preeclampsia - Aneman, Ingrid; Pienaar, Dillan; Suvakov, Sonja; Simic, Tatjana P.; Garovic, Vesna D.; McClements, Lana (Frontiers in Immunology, 2020)
Preeclampsia is a complex cardiovascular disorder of pregnancy with underlying multifactorial pathogeneses; however, its etiology is not fully understood. It is characterized by the new onset of maternal hypertension after 20 weeks of gestation, accompanied by proteinuria, maternal organ damage and/or uteroplacental dysfunction. Preeclampsia can be subdivided into early- and late-onset phenotypes, diagnosed before 34 weeks or from 34 weeks of gestation, respectively. Impaired placental development in early pregnancy and subsequent growth restriction is mainly associated with EOPE, while LOPE is associated with maternal endothelial dysfunction. These two phenotypes have some overlapping and distinct features in terms of pathogenesis. The innate immune system plays an essential role in normal progression of physiological pregnancy and fetal development. However, inappropriate or excessive activation of this system can lead to placental dysfunction or poor maternal vascular adaptation and contribute to the development of preeclampsia. This review aims to comprehensively outline the mechanisms of key innate immune cells including macrophages, neutrophils, natural killer (NK) cells and innate B1 cells, in normal physiological pregnancy, early- and late-onset preeclampsia. The roles of the complement system, syncytiotrophoblast extracellular vesicles and mesenchymal stem cells (MSCs) are also discussed in the context of innate immune system regulation and preeclampsia. The outlined molecular mechanisms, which represent potential therapeutic targets, and associated emerging treatments, are evaluated as treatments for preeclampsia. Therefore, by addressing the current understanding of innate immunity in the pathogenesis of early- and late-onset preeclampsia, this review will contribute to the body of research that could lead to the development of better diagnosis, prevention and treatment strategies. Importantly, it will delineate the differences in the mechanisms of the innate immune system in two different types of preeclampsia, which is necessary for a more personalized approach to the monitoring and treatment of affected women.